(untitled) (Global Journal of Management and Business Research, 2013)
This study is done to examine the perceived service quality and purchasing aspects in various retail stores. This study becomes an important study as it helps in examining the differences among many variables of perceived service quality and purchasing aspects in retailing across the various demographic profiles. This study was carried out in three states. These three states are Delhi, Haryana (Gurgaon & Faridabad) and U.P. (Noida & Ghaziabad). A total sample size of 600 customers was chosen from seven organized stores in these three states. Finally 540 responses were received from these states. It gave a response rate of 90% in total. The data was analyzed with the help of proper statistical tools like descriptive statistics, Mean and Kruskal-Wallis test with One Way ANOVA was used.